Legislative assessments as a tool for strengthening health security capacity: the example of Guinea post-2014 Ebola outbreak - Aurelia Attal-Juncqua; Claire J Standley; Anna Tordjmann; Gian L Burci; Rebecca Katz (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background An effective and dedicated legislative framework is necessary to give effect to the obligations under Articles 5 and 13 of the International Health Regulations (IHR) and is an indicator under the prevent pillar of the Joint External Evaluation (JEE) tool. Following the 2014-2016 Ebola crisis in West Africa, the President of Guinea established a new agency solely dedicated to preparedness and response to public health emergencies. This paper presents the results of a research project to assess the legal and regulatory basis for activities related to public health emergencies management across the Guinean government. # Methods A literature review, combined with in-country consultations, individual interviews and a stakeholder workshop was used to identify and analyze legislation related to the management of public health emergencies in Guinea. Once key gaps and overlaps between existing legal and regulatory documents were identified, we categorized them under the JEE key technical areas. We then identified and reviewed examples of best practices in health emergency legislation for corresponding technical areas from other African and Asian countries. # Results In 14 out of the 19 JEE technical areas, we identified key legislative gaps and potential areas of conflicting authorities within and between ministries. Most consequentially, we identified a lack of formal legislation or mechanisms to support information and data sharing within and between agencies and sectors as well as relevant authorities in neighboring countries, despite the benefits such mechanisms may offer for improved communication when public health emergencies threaten to cross borders. The legislative review also enabled the identification of possible gaps in corresponding foreign legislation, illustrating that this type of assessment may have larger regional or even global implications, in terms of identifying priority areas for future legislative development across diverse legal systems and access to resources. # Conclusions This legislative review allowed for the identification of numerous legislative gaps that, if filled, could support the government to be better equipped to protect the health and life of Guineans in health emergencies. Importantly, our paper serves to demonstrate the utility of legislative assessment as an essential and effective tool for strengthening health security capacity more broadly.